Pemanfaatan Teknologi Pengolahan Limbah Sereh Wangi Menjadi Pupuk Organik - Juliadri, Juliadri (Jurnal Global Ilmiah, 2025)
The use of citronella waste as raw material for organic fertilizer is an innovative solution in managing waste and improving soil quality in an environmentally friendly manner. This study aims to examine the potential of processing lemongrass waste into organic fertilizer, by utilizing efficient and economical technology. The processing process involves fermentation techniques and decomposition of organic matter that can convert lemongrass waste into nutrient-rich fertilizer. The results of the study show that organic fertilizer from citronella waste can increase soil fertility, improve soil structure, and have a positive impact on plant growth. The technology applied in this study makes a significant contribution to agricultural waste management and supports sustainable agriculture. The use of citronella waste as an organic fertilizer also has wide market potential, considering the increasing demand for organic fertilizer products.